Pulmonary hypertension in the intensive care unit. Expert consensus statement on the diagnosis and treatment of paediatric pulmonary hypertension. The European Paediatric Pulmonary Vascular Disease Network, endorsed by ISHLT and DGPK. (6th April 2016) - Kaestner, Michael; Schranz, Dietmar; Warnecke, Gregor; Apitz, Christian; Hansmann, Georg; Miera, Oliver
Abstract : Acute pulmonary hypertension (PH) complicates the course of several cardiovascular, pulmonary and other systemic diseases in children. An acute rise of RV afterload, either as exacerbating chronic PH of different aetiologies (eg, idiopathic pulmonary arterial hypertension (PAH), chronic lung or congenital heart disease), or pulmonary hypertensive crisis after corrective surgery for congenital heart disease, may lead to severe circulatory compromise. Only few clinical studies provide evidence on how to best treat children with acute severe PH and decompensated RV function, that is, acute RV failure. The specific treatment in the intensive care unit should be based on the underlying pathophysiology and not only be focused on so-called 'specific' or 'tailored' drug therapy to lower RV afterload. In addition therapeutic efforts should aim to optimise RV preload, and to achieve adequate myocardial perfusion, and cardiac output. Early recognition of patients at high risk and timely initiation of appropriate therapeutic measures may prevent the development of severe cardiac dysfunction and low cardiac output. In patients not responding adequately to pharmacotherapy, (1) novel surgical and interventional techniques, temporary mechanical circulatory support with extracorporeal membrane oxygenation, (2) pumpless lung assist devices (3) and/or lung or heart-lung transplantation should be timely considered. The invasive therapeutic measures can be applied in a bridge-to-recovery or bridge-to-lung transplant strategy. This consensus statement focuses on the management of acute severe PH in the paediatric intensive care unit and provides an according treatment algorithm for clinical practice.